PENGATURAN KENAIKAN PANGKAT PEGAWAI NEGERI SIPIL PENYESUAIAN IJAZAH (Sesuai Dengan Peraturan Pemerintah Nomor 12 Tahun 2002 Tentang Kenaikan Pangkat Pegawai Negeri Sipil) - I Dewa Ketut Widana (Kerta Dyatmika, 2020)
Abstract The ability of the Civil Servants can be improved, one of which is through promotion according to the level of service and adjustment of the diploma obtained. In the general explanation of Government Regulation Number 12 of 2002 concerning Amendments to Government Regulation Number 99 of 2000 concerning Promotion of Civil Servants explained the promotion is an award given for the work performance and dedication of the concerned Civil Servants to the State. in addition, promotion is also intended as an encouragement to Civil Servants to further improve their work performance and service. Based on the background of the problem, the formulation of the problem in this study is as follows: how to regulate the promotion of Civil Servants based on diploma adjustments in accordance with Government Regulation Number 12 of 2002 concerning Promotion of Civil Servants and whether constraints in promotion through diploma adjustment are appropriate with Government Regulation Number 12 of 2002 concerning Promotion of Civil Servants. The type of research used in this study is normative legal research, meaning that the study in this study is based on legal philosophy, legal principles, and applicable legal norms relating to the regulation of promotion of civil servants based on diploma adjustments. This research used a statute approach, a historical approach and a conceptual approach. The conclusion of this study is the regulation of the promotion of Civil Servants based on diploma adjustments, given to Civil Servants who obtain Higher Learning Certificates / Diplomas that are higher than the diplomas used when applying to become Civil Servants. For example, candidates for Civil Servants when appointed as high school / senior high school civil servants, with rank / class II / a, after + 5 years of work obtain a S1 diploma, if adjusted for the diploma be the rank / class III / a Civil Servants. To obtain a higher rank / class of civil servants / or a level higher than the previous rank / class can be carried out if the diploma obtained is in accordance with the Job Job occupied by the civil servant, there is a formation in that place, has permission to study for those who continuing education and having fulfilled a minimum of 3 (three) years in service. Keywords: Promotion, Civil Servants and Diplomas